ASSOCIATIONS BETWEEN MACULAR EDEMA AND CIRCULATORY STATUS IN EYES WITH RETINAL VEIN OCCLUSION: An Adaptive Optics Scanning Laser Ophthalmoscopy Study. Issue 10 (October 2017) - Iida, Yuto; Muraoka, Yuki; Uji, Akihito; Ooto, Sotaro; Murakami, Tomoaki; Suzuma, Kiyoshi; Tsujikawa, Akitaka; Arichika, Shigeta; Takahashi, Ayako; Miwa, Yuko; Yoshimura, Nagahisa
Abstract : Purpose: To investigate associations between parafoveal microcirculatory status and foveal pathomorphology in eyes with macular edema (ME) secondary to retinal vein occlusion (RVO). Methods: Ten consecutive patients (10 eyes) with acute retinal vein occlusion were enrolled, 9 eyes of which received intravitreal ranibizumab (IVR) injections. Foveal morphologic changes were examined via optical coherence tomography (OCT), and parafoveal circulatory status was assessed via adaptive optics scanning laser ophthalmoscopy (AO-SLO). Results: The mean parafoveal aggregated erythrocyte velocity (AEV) measured by adaptive optics scanning laser ophthalmoscopy in eyes with retinal vein occlusion was 0.99 ± 0.43 mm/second at baseline, which was significantly lower than that of age-matched healthy subjects (1.41 ± 0.28 mm/second, P = 0.042). The longitudinal adaptive optics scanning laser ophthalmoscopy examinations of each patient showed that parafoveal AEV was strongly inversely correlated with optical coherence tomography-measured central foveal thickness (CFT) over the entire observation period. Using parafoveal AEV and central foveal thickness measurements obtained at the first and second examinations, we investigated associations between differences in parafoveal AEV and central foveal thickness, which were significantly and highly correlated (r = −0.84, P = 0.002). Conclusion: Using adaptive optics scanning laser ophthalmoscopy in eyes with retinal vein occlusion macular edema, we could quantitatively evaluate the parafoveal AEV. A reduction or an increase in parafoveal AEV may be a clinical marker for the resolution or development/progression of macular edema respectively. Abstract : Supplemental Digital Content is Available in the Text.Adaptive optics scanning laser ophthalmoscopy enabled objective measurements of the absolute velocity of parafoveal aggregated erythrocyte in eyes with retinal vein occlusion-associated macular edema. Velocity changes were strongly associated with macular edema changes.